(untitled) - Walter, G. H. (Cambridge, UK, 2003)
Insect Pest Managament and Ecological Research develops the first general model of the entomological research requirements of Integrated Pest Management (IPM). It shows how to navigate the diversity of options presented by current ecological theory, emphasising pest situations. The book also includes practical advice on understanding and investigating species, examines the ecological problems associated with polyphagous pests and beneficial species, and scrutinises ways suggested to improve insect biological control. It will be an important resource for graduate students and researchers, in IPM, insect pest management, entomology, ecology and crop protection.
Keywords: Insect pests,Insect pests; Integrated control,Ecology